The Pearl : A Failed Slave Escape on the Potomac - Pacheco, Josephine F. (Book collections on Project MUSE., 2005)
In 1848 seventy-six slaves from the nation's capital hid aboard the schooner Pearl in an attempt to sail to freedom in Pennsylvania. When bad weather forced them to anchor, the slaves and the ship's crew were captured and returned to Washington. This work ranges from the preparations for escape to the participants' trial.